Od pašnika do odra - Klobčar, Marija (Traditiones (Ljubljana), 2000)
The article focuses on the question how uneducated people changed their attitude toward folk culture from being subconsciously rooted in it to deliberately discovering it, and how the creativity of an individual wished to copy or even supplant folk culture. The path from "the pasture to the stage" contains two meaning: while being the true life path of Kati Turk whose life and work is used as an illustration of the above-mentioned problem, it is also a symbolically-termed distance between folklore and folklorism or, better yet, between folk and mass culture
Keywords: ljudsko izročilo; množična kultura